Top incomes in Central Africa: Historical evidence - (:unkn) unknown (My University, 2015)
This paper presents new historical evidence about the distribution of income in the three former British colonial territories of Central Africa: Malawi, Zambia and Zimbabwe. Zimbabwe in its colonial period, under its then name of Southern Rhodesia, was a highly unequal country, but little is known about just how unequal it was. According to Kuznets (1963, Table 3), in 1946 the white settlers made up some 5 per cent of the population and received 65.3 per cent of total income. But how was this distributed among the settler population? How did the distribution change over the colonial period? What was the distributional impact of the Unilateral Declaration of Independence (UDI) and the ensuing civil war? Northern Rhodesia, now Zambia, featured in Table 3 of Kuznets (1963) as having a share of the top 5 per cent in 1946 of 45.3 per cent, exceeded only by Southern Rhodesia. The Kuznets figure for Northern Rhodesia was based solely on total non-African and African incomes, and, as he clearly recognises, understates the true inequality. It tells us nothing about the inequality within these groups. Europeans in the mining industry may well have been paid considerably more than those in the government service. Equally, in the case of Malawi, previously Nyasaland, we know little about the extent of income inequality before and after the country became independent in 1964.
Keywords: African Research